Molecular epidemiology of avian influenza viruses and risk mapping in Mali and West Africa - (:unkn) unknown (My University, 2023)
Avian influenza viruses represent a major threat to human and animal health. These viruses are responsible for high morbidity and mortality, especially in the poultry industry, resulting in huge economic losses. West Africa is a region with little information on the circulation and genetic characteristics of avian influenza viruses, despite the occurrence of several outbreaks in birds. In this thesis, we studied the circulation and genetic characteristics of avian influenza viruses of subtypes H5N1 and H9N2 circulating in West Africa. We also developed a model to map the risk of the spread of these viruses. The genetic and antigenic characteristics of the influenza viruses were determined by molecular characterization and phylogenetic and phylogeographic analysis. The H5N1 virus found in Benin in 2021 was highly pathogenic, belonged to the GS/GD lineage - clade 2.3.4.4.B, and was closely related to contemporary H5N1 viruses detected in West Africa and Europe. This virus had a mammalian adaptation mutation (on the PB1 protein) and an antigenic profile that differed from the vaccine strains recommended by the World Health Organization as part of pre-pandemic preparedness. The H9N2 viruses detected in poultry in Mali belonged to the G1 lineage and also possessed several molecular markers of virulence and adaptation to mammals. In particular, we have found a motif (RSNR) at the cleavage site of the haemagglutinin of these viruses that had not previously been detected in Africa. Analysis of the spatiotemporal dynamics of H9N2 viruses revealed that they were probably introduced into West Africa in 2015 from Morocco. Finally, we implemented the risk mapping model, based on the multicriteria decision analysis method associated with geographic information systems, to produce risk maps for the introduction and spread of avian influenza in Mali. This model can be used as a basis for implementing risk-based surveillance of avian influenza viruses.In conclusion, th
Keywords: African Research